Three Finnish graphemic first name categories and models: classification and popularity variation - Szabó, Edla (Hungary, 2026)
Finnish personal names can be classified into graphemic first name categories and graphemic first name models. In this article, three of these categories, ELLA, HELMI and EETU, and six models, “ella”, “anni”, “emma”, “helmi”, “lilja” and “eetu” are discussed. “ella”, “anni” and “emma” belong to the graphemic first name category ELLA, “helmi” and “lilja” to the graphemic first name category HELMI and “eetu” to the graphemic first name category EETU.
The categories and models in this article consist of the most popular Finnish first names from the years between 2000 and 2020. Because of this, the chosen categories and models represent two popular Finnish naming trends in the 2000s: the voiced consonants l, m and n trend and the long vowel ee trend. The models “ella”, “anni”, “emma”, “helmi” and “lilja” represent the voiced consonants trend and the model “eetu” the ee trend.
The temporal popularity variation is depicted with three models, “anni”, “helmi” and “eetu”. “anni” represents the decreasing trend of names with nn and “helmi” the increasing trend of names with lm. “eetu” shows that names containing ee are popular throughout the whole 2000–2020 period.
Onomastica Uralica 17